PENGARUH METODE GURU PAK DALAM MENGAJAR TERHADAP MOTIVASI BELAJAR PESERTA DIDIK - walangitan, Nofry; Fung, Lim Siauw (Sekolah Tinggi Teologi Hagiasmos Mission, 2022)
Good teachers use a variety of learning methods that will make students enthusiastic in understanding learning. Using a variety of methods in teaching is very necessary considering that students also have a variety of learning methods as well. Some are easier to understand when taught by visual methods (for example with videos, pictures, etc.), audio (for example by lecturing, listening to songs, and others). , and kinesthetic (eg by combining sports activities with learning materials). In the context of Christian religious education, varied methods make the material presented can be understood and understood, even applied by students. There are various methods that can be used, including: lecture, question and answer, discussion, dialogue, demonstration, and other models. This research was conducted at SDN No 078580 Tetehili, South Nias Regency to determine the effect of Christian religious education teacher methods on learning motivation at SDN No 078580 Tetehili, South Nias Regency. This research was conducted with quantitative methods. After conducting the research, it was found that the average value of PAK teachers' teaching methods in teaching at SDN No.078580 Tetehili, South Nias Regency was strong. This has a positive impact, namely the learning motivation of students at SDN No. 078580 Tetehili, South Nias Regency is tegolong strong.